2019
DOI: 10.3390/molecules24244520
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine Eliminates Colon Cancer Stem Cells via Suppressing Notch and Wnt Signaling

Abstract: Evodiamine, an alkaloid contained in traditional Asian herbal medicines that have been used for hundreds years, is interesting due to its cytotoxic effects against many cancers. We examined the effect of evodiamine on the cancer stem cell (CSC) population and the bulk cultured cancer cells (BCC) of colon cancers to examine the double targeting effect. We found that three colon cancer cell lines’ BCC and CSC are effectively targeted by evodiamine. Evodiamine was able to suppress BCC proliferation and induce apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…They were maintained as bulk culture cells (BCC) in Dulbecco’s modified eagle’s medium (DMEM, Invitrogen, Waltham, MA, USA) or RPMI 1640 (Invitrogen) supplemented with FBS (Fetal bovine serum, Invitrogen). For cancer stem cell (CSC) enrichment, they were cultured in DMEM/F12 containing B27 supplement and 20 ng/mL EGF (all from Invitrogen) in a polyHEMA (Sigma–Aldrich, St. Louis, MO, USA)-coated dish as described previously [ 20 ]. All cultured cells were maintained at 37 °C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were maintained as bulk culture cells (BCC) in Dulbecco’s modified eagle’s medium (DMEM, Invitrogen, Waltham, MA, USA) or RPMI 1640 (Invitrogen) supplemented with FBS (Fetal bovine serum, Invitrogen). For cancer stem cell (CSC) enrichment, they were cultured in DMEM/F12 containing B27 supplement and 20 ng/mL EGF (all from Invitrogen) in a polyHEMA (Sigma–Aldrich, St. Louis, MO, USA)-coated dish as described previously [ 20 ]. All cultured cells were maintained at 37 °C in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The cells were reverse transfected with siSCD1, and siControl (NC) obtained from IDT (Coralville, IA, USA) using Lipofectamine ® RNAiMAX (Thermo, Waltham, MA, USA) in accordance with the manufacturer’s protocol. Cell viability was evaluated as previously published [ 20 ]. Four thousand cells were seeded in every well of a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Verteporfin can inhibit the transcriptional activity of YAP/TAZ-TEAD, reduce the expression of CSC markers, and suppress CSC proliferation [108,109]. Evodiamine (Evo), which is isolated from the Chinese herb Evodia rutaecarpa Benham, can activate MST1/2-mediated phosphorylation of LATS1/2, which leads to YAP/TAZ phosphorylation and prevents YAP/TAZ translocation from the cytoplasm into the nucleus, and it has been shown that Evo can inhibit the proliferation of colon CSCs [110,111]. Additionally, tanshinone IIA and limonin, which are extracted from Chinese herbs, have been shown to attenuate the stemness of cervical carcinoma stem cells by inhibiting the cytoplasmic-nuclear translocation of YAP [112,113].…”
Section: Hh Signaling Pathway Inhibitorsmentioning
confidence: 99%
“…As a potential factor in cell fate, increasing evidence has shown that Notch signaling plays like a double-edged sword in cancer, and it has both oncogene and onco-suppressor activities [ 248 , 249 , 250 , 251 , 252 , 253 , 254 ]. It has been reported that metastasis of GC cells is tightly regulated by Notch/PTEN/Akt axis.…”
Section: Upstream Modulators Of Ptenmentioning
confidence: 99%